Conceptual structure and perspectives on entrepreneurship education research: A bibliometric review - Gloria Aparicio; Txomin Iturralde; Amaia Maseda (European Research on Management and Business Economics (ERMBE), 2019)
This study aims to review the field of Entrepreneurship Education (EE). The review examines 325 scientific articles published in refereed scientific journals from 1987 to 2017. The SciMat software was used to conduct an analysis of performance indicators and science mapping visualizations. The performance analysis results identified some of the field's most active and influential articles, journals, and authors. The science mapping visualization of co-word analysis results revealed EE research evolution. In general, we found that EE research has evolved from EE as part of an economic development strategy to the EE academic perspective. Furthermore, research themes showed that students, rather than teachers, have become the main agents of the educational process. The results of this bibliometric analysis enhance understanding of the evolution of EE research with a global overview of the relevant literature and its authors.
Keywords: 650; Entrepreneurship education; Entrepreneurial intention; Entrepreneurial learning; Bibliometrics; SciMat